What is an academic book publisher? An Ibero-American contribution to the definition - Esteban Giraldo-González; Elea Giménez-Toledo; Juan Felipe Córdoba-Restrepo (Insights: The UKSG Journal)
This article discusses attempted definitions of what an academic publishing house is. The wide range of views about the issue, as expressed by editors, authors and institutions, are reviewed and the reasons why they are not satisfactory to develop a comprehensive view of the sector are explained. Then, following a quantitative analysis of ISBN databases and qualitative work conducted through focus groups with experts from nine countries – developed as part of the Cartography of Ibero-American Academic Publishing project – it presents a three-criteria list: the availability of title lists, publication of academic research and funding status. These criteria can help to identify a publishing house as properly academic. Such criteria may contribute significantly to consolidating studies on the sector and to promoting the recognition of academic publishing by the entities that evaluate and generate public policies on science, technology and knowledge dissemination in Ibero-American countries.